Answer:
(3x+1)(x+3) is the factorised form for the expression.
Step-by-step explanation:
:3
x
2
+
10
x
+
3
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
is the factorised form for the expression.
Yea they are i would type more but here
Answer:
That's incorrect. The simplest way to show this is by evaluating the functions at a given point. Let's say x=0, then:
Sin(-x) = Sin(0) = 0
-cos x = -cos (0) = -1
Therefore, Sin(-x)≠-cos x.
1= 4/4 therefore 2=8/4
8/4 + 1/4 = 9/4
So Steve bought 9/4 of pizza total
I think it’s is c I’m not sure tho